The foreign messiah of "El Economista" (1895) The first economics seminar in Peru - Sato Kuroda, Enrique (2007)
The article is an analysis of "El Economista", the first economics seminar in the country, specifically during its first two years. It begins by describing the graphic and administrative characteristics of the magazine. Subsequently and in a fundamental way, it summarizes the articles that present their economic alternative, which the article calls pro-imperialist liberal and which, at its extreme, and through the promotion of white immigration, would have led to the expectation of a foreign Messiah. as the basis of the economic development of the country. It frames the alternative in the changes that occurred in the world economy, with the rise of imperialism, and during the years in which what some call the first economic globalization took place. Apparently, this phenomenon would have generated in the dominant sectors, the same illusions in international capital and in everything external, that are presented in the current phase of globalization of the world economy.